Influence of job demands, job resources, and personal resources on air traffic controllers’ job stress and job performance in Saudi Arabia - Alaydi, Bader Ibrahim S (2022)
Air Traffic Control (ATC) is a major component of the aviation industry as it plays a substantial role in ensuring flight safety. If ATC performance is compromised, tragedies may happen. As a result, ATC is recognized universally as a highly stressful occupation. Based on the job demands-resources theory (JDR), a framework was developed to investigate the impacts of job complexity, mental workload, mindfulness, and training on job stress and job performance, via the moderating role of intra-functional flexibility and social work support. Although many studies have investigated the relationships between job complexity, mental workload, training, mindfulness, stress and job performance, there remain several unaddressed gaps related to conflicting findings on the mental workload–job performance, job complexity–job performance, mindfulness– job stress, and mindfulness–job performance relationships. Also, the literature calls for more investigations on the moderating roles of intra-functional flexibility and social work support, given the importance of understanding the conditions that influence the job stress–performance relationship in Saudi Arabian ATC. The study was conducted on air traffic controllers across ATC units in Saudi Arabia using the proportional stratified sampling technique. The sample size comprised 450 air traffic controllers, from whom 324 questionnaires were received with no missing data, yielding a response rate of 72 percent. The analysis results indicate that most of the findings are in line with the JDR model and previous studies. Furthermore, it was found that intra-functional flexibility and social work support weaken the health impairment process while intra-functional flexibility strengthens the motivational process, as expected. However, there were a few surprising results; for example, job stress only mediated the relationship between training and job performance, whereas mindfulness only exhibited a positive influence on job performance and showed no effect on job stress. This study contributes to the literature in four ways. First, it extends the JDR theory to the ATC context. Second, the JDR health impairment process (demand-stress-performance) was tested using job stress as mediator, and new job demand (job complexity) and personal resource (mindfulness) variables were introduced to the JDR model. Third, the study verified critical linkages between mental workload–job performance, job complexity–job performance, mindfulness–job stress, and mindfulness–job performance. Fourth, the boundary conditions (social work support and intra-functional flexibility) that alter the relationships proposed by the JDR model were identified. Theoretical implications, practical recommendations to ATC organizations, and limitations and future research are discussed.